2002
DOI: 10.1093/pcp/pcf060
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Binding Proteins for N-Acetylchitooligosaccharide Elicitor in the Plasma Membranes from Wheat, Barley and Carrot Cells: Conserved Presence and Correlation with the Responsiveness to the Elicitor

Abstract: Binding experiments as well as affinity labeling with an (125)I-labeled 2-(4-aminophenyl)ethylamino derivative of N-acetylchitooctaose revealed the presence of high-affinity binding sites/proteins for N-acetylchitooligosaccharide elicitor in the plasma membrane preparation from suspension-cultured carrot cells, barley cells and wheat leaves. Their binding specificity corresponded with the elicitor activity of N-acetylchitooligosaccharides and related sugars in these plant cells/tissues, and was similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 29 publications
2
49
0
2
Order By: Relevance
“…Similar binding proteins were also detected in various plant cells that could respond to the elicitor (8,9). Correlation between the presence of the binding proteins and the elicitor responsiveness of these cells, correlation between the binding specificity and the preference of the structure of chitin oligosaccharides in defense responses, strongly indicated that the binding proteins function as a receptor, or a part of receptor complex, for chitin oligosaccharide elicitor.…”
mentioning
confidence: 61%
“…Similar binding proteins were also detected in various plant cells that could respond to the elicitor (8,9). Correlation between the presence of the binding proteins and the elicitor responsiveness of these cells, correlation between the binding specificity and the preference of the structure of chitin oligosaccharides in defense responses, strongly indicated that the binding proteins function as a receptor, or a part of receptor complex, for chitin oligosaccharide elicitor.…”
mentioning
confidence: 61%
“…Whether chitosan oligomers killed cells by activating an H 2 O 2 -independent PCD or simply by necrosis is still unknown in our system. Unlike N-acetyl-chitooligosaccharides for which a receptor has been identified (Okada et al 2002), the way chitosan oligomers are perceived by plant cells is still unknown and often considered as a non-specific interaction of a polycation with negatively charged plasma membrane phospholipids that mimics and activates a common MAP kinase-dependent defence response (Shibuya and Minami 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the availability of chitinases and other chitin hydrolytic or binding activities in the plant cell wall could drastically reduce the elicitor concentration effectively perceived by the protoplast. The level of expression of oligochitin receptors (Bradley Day et al 2001, Okada et al 2002, or of other oligochitin-binding proteins Claeson 2003, Peumans et al 2003), could be developmentally regulated and also explain the discrepancies between different plant models (cell suspensions, seedlings and whole plants) and plant species. For example, Okada et al (2002) showed that carrot, wheat, barley, rice and tobacco BY-2N cells responded differently to N-acetyl-chitooligosaccharides, although their plasma membranes all contained a high-affinity binding site for N-acetyl-chitooligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using radiolabeled b-1,3-glucan and hepta-b-glucoside elicitors characterized from fungal cell walls of Phytophthora megasperma f sp glycinea (Schmidt and Ebel, 1987), high affinity binding proteins have been identified in isolated legume plasma membrane fractions (Cheong and Hahn, 1991;Cote et al, 2000). Elicitor binding receptors for the N-acetylchitooligossaccharide elicitor have also been detected in plasma membrane fractions from several plant species including Oryza sativa (rice), Triticum aestivum (wheat), Hordeum vulgare (barley), and Daucus carota (carrot) (Okada et al, 2001(Okada et al, , 2002. Each of these pathogen elicitor-plant receptor interactions is characterized by nanomolar EC 50 concentrations as well as K d values in the low nanomolar range.…”
Section: Discussionmentioning
confidence: 99%